The application of microwave heating in bioenergy: A review on the microwave pre-treatment and upgrading technologies for biomass - Kostas, Emily T.; Beneroso, Daniel; Robinson, John P. (Elsevier, 2017)
Bioenergy, derived from biomass and/or biological (or biomass-derived) waste residues, has been acknowledged as a sustainable and clean burning source of renewable energy with the potential to reduce our reliance on fossil fuels (such as oil and natural gas). However, many bioenergy processes require some form of pre-treatment and/or upgrading procedure for biomass to generate a modified residue with more suitable properties and render it more compatible with the specific energy conversion route chosen. Many of these pre-treatments (or upgrading procedures) involve some form of substantive heating of the biomass to achieve this modification. Microwave (MW) heating has attracted much attention in recent years due to the advantages associated with dielectric heating effects. These advantages include rapid and efficient heating in a controlled environment, increasing processing rates and substantially shortening reaction times by up to 80%. However, despite this interest, the growth of industrial MW heating applications for bioenergy production has been hindered by a lack of understanding of the fundamentals of the MW heating mechanism when applied to biomass and waste residues. This article presents a review of the current scientific literature associated with the application of microwave heating for both the pre-treatment and upgrading of various biomass feedstocks across different bioenergy conversion pathways including thermal and biochemical processes. The fundamentals behind microwave heating will be explained, as well as discussion of the imperative areas which require further research and development to bridge the gap between fundamental science in the laboratory and the successful application of this technology at a commercial scale.